Macropod management is critical for recovery of Sheoak Grassy Woodlands on Eyre Peninsula, South Australia. (2nd November 2021) - Freeman, Andrew; Pobke, Katrina
Summary: The relative impacts of kangaroos ( Macropus and Osphranter spp.) and introduced mammalian herbivores on the success of two South Australian landscape‐scale vegetation restoration projects were investigated using herbivore exclusion plots, herbivore scat counts and spotlight counts. The results confirm that kangaroos in high abundance have replaced introduced herbivores as the major element in total grazing pressure that is preventing the recovery of degraded native vegetation communities. These projects demonstrate the need for monitoring and adaptive management of kangaroos for the success of rehabilitation programmes.